2015
DOI: 10.1016/j.jobcr.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Pre-arthroplastic and simultaneous mandibular distraction for correction of facial deformity in temporomandibular joint ankylosis

Abstract: a b s t r a c tIntroduction: In cases of temporomandibular joint (TMJ) ankylosis, interposition arthroplasty allows return of functional jaw movements. In order to improve the facial appearance, distraction osteogenesis is the treatment of choice, and may be timed either as a prearthroplastic, simultaneous or post-arthroplastic procedure. This study was planned to compare the treatment outcomes of pre-arthroplastic distraction (PAD) and simultaneous arthroplastic distraction (SAD) to establish the better treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…The two RCTs included were by Chellappa et al, 3 where prearthroplasty and simultaneous arthroplasty mandibular distraction was compared, and other by Kaur et al 4 ) with random effect model (Fig. 2b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The two RCTs included were by Chellappa et al, 3 where prearthroplasty and simultaneous arthroplasty mandibular distraction was compared, and other by Kaur et al 4 ) with random effect model (Fig. 2b).…”
Section: Resultsmentioning
confidence: 99%
“…Prearthroplastic DO 3,[23][24][25][26][27][28][29][30][31][32][33][34][35] : Pre-arthroplasty distraction is preferred for multiple reasons. It allows distraction against a stable fixed point, such that a true distraction of mandible occurs and that too in the desired direction only, and with a better vector control.…”
Section: Mandibular Distraction Osteogenesis For Facial Deformity Correctionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Cases with associated facial deformity are either managed by a Le Fort I osteotomy and its inferior positioning ipsilaterally or bilaterally for correction of occlusal cant along with inverted L osteotomy of ramus or with pre-arthroplastic mandibular or maxillomandibular distraction osteogenesis (DO). 8 11…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous arthroplasty and MDO enable the production of a neocondyle and allow for concomitant correction of facial malformations. The treatment outcomes of pre-arthroplastic distraction and simultaneous arthroplastic distraction have been previously compared and it was concluded that the two methods were effective in correcting the aesthetics of the patients and functional movement of the TMJ (13). Papageorge and Apostolidis (14) were the first to perform simultaneous gap arthroplasty and MDO for the treatment of micrognathia in ankyloses of the TMJ in 1999; as a result, mouth opening was improved and facial deformity was corrected.…”
Section: Discussionmentioning
confidence: 99%